The political economy of health financing reform in Malaysia. Issue 10 (28th September 2019) - Croke, Kevin; Mohd Yusoff, Mariana Binti; Abdullah, Zalilah; Mohd Hanafiah, Ainul Nadziha; Mokhtaruddin, Khairiah; Ramli, Emira Soleha; Borhan, Nor Filzatun; Almodovar-Diaz, Yadira; Atun, Rifat; Virk, Amrit Kaur
Abstract: There is growing evidence that political economy factors are central to whether or not proposed health financing reforms are adopted, but there is little consensus about which political and institutional factors determine the fate of reform proposals. One set of scholars see the relative strength of interest groups in favour of and opposed to reform as the determining factor. An alternative literature identifies aspects of a country's political institutions–specifically the number and strength of formal 'veto gates' in the political decision-making process—as a key predictor of reform's prospects. A third group of scholars highlight path dependence and 'policy feedback' effects, stressing that the sequence in which health policies are implemented determines the set of feasible reform paths, since successive policy regimes bring into existence patterns of public opinion and interest group mobilization which can lock in the status quo. We examine these theories in the context of Malaysia, a successful health system which has experienced several instances of proposed, but ultimately blocked, health financing reforms. We argue that policy feedback effects on public opinion were the most important factor inhibiting changes to Malaysia's health financing system. Interest group opposition was a closely related factor; this opposition was particularly powerful because political leaders perceived that it had strong public support. Institutional veto gates, by contrast, played a minimal role in preventing health financing reform in Malaysia. Malaysia's dramatic early success at achieving near-universal access to public sector healthcare at low cost created public opinion resistant to any change which could threaten the status quo. We conclude by analysing the implications of these dynamics for future attempts at health financing reform in Malaysia.